Pengaruh struktur modal, profitabilitas, kebijakan utang, pertumbuhan perusahaan, dan ukuran perusahaan terhadap nilai perusahaan - Abdul Malik Kumar; Jessicha Chechelia Jelita Putri; Sunaryari Hardiani (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2024)
The aim of this research is to analyze the influence of capital structure, profitability, debt policy, company growth and company size on firmvalue. The population and sample used in this research are food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample for this research was 11 companies with 54 data obtained using the purposive sampling method. The data analysis used is multiple linear regression analysis. The results of the research show that capital structure and profitability have a positive effect on company value. Meanwhile, debt policy, company growth and company size have a negative effect on firm value.